2021
DOI: 10.3389/fmed.2021.646220
|View full text |Cite
|
Sign up to set email alerts
|

Risks of Placenta Previa and Hypertensive Disorders of Pregnancy Are Associated With Endometrial Preparation Methods in Frozen-Thawed Embryo Transfers

Abstract: Background: Endometrial preparation is essential in frozen-thawed embryo transfer (FET) cycles. Recent studies suggested that different endometrial preparation methods may influence obstetrical complications. However, the association between hormone replacement therapy (HRT) and ovarian stimulation (OS) FET endometrial preparation and obstetrical complications remains unknown.Methods: This retrospective cohort study included a total of 79,662 confirmed embryo transfer cycles during the period from January 2003… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…The results showed that HRT cycles had similar possibilities of biochemical pregnancy, clinical pregnancy, abortion, and live birth compared to the natural cycles, regardless of whether day 3 cleavage stage embryos or day five or six blastocyst stage embryos were transferred. Previous studies showed that the HRT protocol was associated with an increased risk of maternal and neonatal complications [17,21] . However, we did not obtain data on pregnancy complications and neonatal outcomes because of the limitations of the retrospective collection of medical records.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that HRT cycles had similar possibilities of biochemical pregnancy, clinical pregnancy, abortion, and live birth compared to the natural cycles, regardless of whether day 3 cleavage stage embryos or day five or six blastocyst stage embryos were transferred. Previous studies showed that the HRT protocol was associated with an increased risk of maternal and neonatal complications [17,21] . However, we did not obtain data on pregnancy complications and neonatal outcomes because of the limitations of the retrospective collection of medical records.…”
Section: Discussionmentioning
confidence: 99%
“…In a big data retrospective analysis conducted in Japan, it was found that, compared with patients with natural ovulation cycle (NC-FET), patients using HRT-FET had an increased risk of HDP and placental implantation, while the risk of GDM was observed to be reduced [ 37 ]. Another retrospective cohort study in China also found that the HRT-FET group had an increased risk of HDP and placenta previa compared to ovarian stimulation in the FET group [ 14 ]. These results suggested that endometrial preparation methods may be related to obstetric complications, especially with respect to the development of HDP.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally believed that the occurrence of HDP may be related to immune system disorder, trophoblast or placental ischemia and oxidative stress [ 11 , 12 ]. Studies have also shown that the incidence of HDP is higher when using assisted reproductive technology (ART), especially in the frozen-thawed embryo transfer (FET) cycle [ 13 ], which may be related to the endometrial preparation protocol in the FET cycle [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…8,26 Gestational diabetes GD was assessed in 17 studies, summarised below in Figure S41. 6,[9][10][11][12][13][14][15][16][17][19][20][21][22][24][25][26] The analysis comparing GD in ArtThawET and NatThawET looked at 38 821 artificial cycles and 48 828 natural cycles, showed a small but significant increase in GD in NatThawET (OR 0.94, 95% CI 0.88, 0.99). There were two studies which compared GD in ArtThawET and FreshET.…”
Section: Post-partum Haemorrhagementioning
confidence: 99%
“…Fifteen studies evaluated PTB as an outcome -the results of these studies are summarised in Figure S40. [6][7]10,[12][13][16][17][19][20][21][22][23][26][27][28] The pooled analysis of PTB comparing ArtThawET and NatThawET included 47 585 artificial cycles and 50 970 natural cycles. The pooled estimate of PTB showed a significant result, with a higher rate of PTB in ArtThawET (OR 1.18, 95% CI 1.13, 1.23).…”
Section: Pre-term Birthmentioning
confidence: 99%